2021
DOI: 10.1101/2021.09.03.21263078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and validation of an enzyme immunoassay for detection and quantification of SARS-CoV-2 salivary IgA and IgG

Abstract: Oral fluids offer a non-invasive sampling method for the detection of antibodies. Quantification of IgA and IgG antibodies in saliva allows studies of the mucosal and systemic immune response after natural infection or vaccination. We developed and validated an enzyme immunoassay (EIA) to detect and quantify salivary IgA and IgG antibodies against the prefusion-stabilized form of the SARS-CoV-2 spike protein. Normalization against total antibody isotype was performed to account for specimen differences, such a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…GCF was inactivated by γ radiation before processing and tested using a validated ELISA against full-length prefusion-stabilized SARS-CoV-2 spike protein. 18 GCF antibodies were reported as a gingival crevicular ratio, defined as SARS-CoV-2 specific Ig per total Ig (ng/100 μg). GCF was first tested for IgA, with the remaining volume used for IgG testing.…”
Section: Methodsmentioning
confidence: 99%
“…GCF was inactivated by γ radiation before processing and tested using a validated ELISA against full-length prefusion-stabilized SARS-CoV-2 spike protein. 18 GCF antibodies were reported as a gingival crevicular ratio, defined as SARS-CoV-2 specific Ig per total Ig (ng/100 μg). GCF was first tested for IgA, with the remaining volume used for IgG testing.…”
Section: Methodsmentioning
confidence: 99%
“…In a pioneer study, Xu et al (2020) demonstrated that the viral load in the salivary fluid is approximately 90%, representing a potential vehicle for SARS-CoV-2 transmission. Other authors also mention the high expression of salivary IgA and IgG antibodies as a form of ensuring the validity of COVID-19 diagnosis (Costantini et al 2021).…”
mentioning
confidence: 99%